Serum iron and risk of nonalcoholic fatty liver disease and advanced hepatic fibrosis in US adults - Huan-Huan Yang (Nature Portfolio, 2021)
Abstract Epidemiological evidence on the relationship between serum iron and liver diseases is limited. This study aims to investigate whether serum iron is associated with nonalcoholic fatty liver disease (NAFLD) and advanced hepatic fibrosis (AHF). Cross-sectional data for adults aged ≥ 18 years who participated in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018 were analyzed. Odds ratio (ORs) and 95% confidence intervals (CIs) of NAFLD and AHF associated with serum iron were estimated using multivariable logistic regression models. A total of 18,031 males and 18,989 females were included in the analysis. After multivariable adjustment for potential confounders, serum iron was significantly and inversely associated with NAFLD in both genders (P-trend < 0.001) and AHF in females (P-trend = 0.018). Compared to the bottom quartile, those in higher quartiles of serum iron had no significant ORs for AHF in males, but the trend across the quartiles was significant (P-trend = 0.046). In conclusion, higher serum iron level was associated with lower risk of NAFLD in males and females, and with lower risk of AHF in females but not in males. No significant racial/ethnical differences in these associations were observed.